2019
DOI: 10.1017/s1368980019003471
|View full text |Cite
|
Sign up to set email alerts
|

A modelling approach to investigate the impact of consumption of three different beef compositions on human dietary fat intakes

Abstract: Objective: To apply a dietary modelling approach to investigate the impact of substituting beef intakes with three types of alternative fatty acid (FA) composition of beef on population dietary fat intakes. Design: Cross-sectional, national food consumption survey – the National Adult Nutrition Survey (NANS). The fat content of the beef-containing food codes (n 52) and recipes (n 99) were updated with FA composition data from beef from animals receiving one of three ruminant dietary inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Consistently across studies, total PUFA content is higher in grass-fed meat, followed by organic meat [39,114,[117][118][119]. A meta-analysis by Średnicka-Tober et al [39] found organic meat to have around 23% more total PUFAs than conventional counterparts.…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 80%
See 1 more Smart Citation
“…Consistently across studies, total PUFA content is higher in grass-fed meat, followed by organic meat [39,114,[117][118][119]. A meta-analysis by Średnicka-Tober et al [39] found organic meat to have around 23% more total PUFAs than conventional counterparts.…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 80%
“…Ribas-Agustí et al [ 40 ] found organic retail beef has 8% fewer SFAs compared with conventional beef and Bjorklund et al [ 113 ] reported organic beef had 23% fewer SFAs than conventional beef from steers of the same breed. One study differentiating pasture-based and non-pasture systems for Angus heifers, found grass-finished cooked beef had 30% fewer SFAs compared to concentrate finished beef [ 114 ]. Additionally, the review by Daley et al [ 115 ] reports no difference in total SFAs between grain-fed and pasture-based beef, but higher concentrations of myristic (C14:0) and palmitic acids (C16:0) (thought to have a greater impact on serum cholesterol [ 115 ]) in intensive grain-fed beef and lower concentrations of stearic acid (thought to have a neutral impact on serum cholesterol [ 115 ]) than in grass-fed beef, suggesting that grass-fed may have a nutritionally favourable SFA profile than grain-fed beef.…”
Section: Effect Of Feed System On Meat Fatty Acid Profilementioning
confidence: 99%
“…Beef from pasture‐based production systems is growing in popularity. Contributory factors include a perception that the cattle are managed in a more environment and animal welfare friendly system, 1 that beef from pasture‐based rather than intensive production systems aligns more closely with human nutrition guidelines with respect to fat consumption, 2 and that beef from pasture‐based production systems looks and tastes differently than beef from intensive production systems. ‘Grass‐fed’ and ‘grass‐based’ are among the labels used on beef products to capture this interest of beef consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Communicating about the positive nutritional attributes of meat can be challenging, however, as the nutritional composition of meat is influenced by management factors, with feeding regimen being particularly significant; grass-based beef, for example, has a different Trends in meat demand and supply 259 nutritional profile from concentrate-fed beef. Based on a modelling approach, Lenighan et al (48) found improved dietary intakes of several fatty acids associated with consuming meat that was grass-fed as opposed to concentrate-fed. Their research led them to conclude that habitual consumption of grass-fed beef may have potential as a public health strategy to improve dietary fat quality.…”
Section: Discussionmentioning
confidence: 99%